Analisis Spasial Dampak Pemekaran Wilayah Terhadap Pertumbuhan Ekonomi Wilayah Kabupaten Tebo Provinsi Jambi - Rena Agus Indarti; Elvi Zuriyani; Rika Despica (FKIP, Universitas Palangka Raya, 2021)
Gross Regional Domestic Product (GRDP) of Tebo regency as a result of regional expansion shows an increase in every year, but developments in the economy show otherwise. Regional Original Income (PAD) in the districtresulting from the division shows a decline in every year. In 1999 the expansion of Bungo -Tebo regency. The aim of this research is to analyze the impact of the regional expansion in economy of Tebo regency before the divisionin 1998, in 2005 after the expansion and the expansion continues. The data that was used in this research is secondary data that consist of data from 1998, 2005, 2020 that obtained from the Central Statistic Agency (BPS)of Tebo regency. The analysis that was used is growth rate of Regional Original Income (PAD) and the growth rate of Gross Regional Domestic Product (GRDP). From the growth rate of GRDP, it experienced growth in 2005after the regional expansion and the growth rate of PAD has not experienced growth after the regional